Spirogyra Link and Sirogonium Kutzing Species: New to Algal Flora of Nepal - Rai, S. K.; Mishra, P. K. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Key words: Algae; Spirogyra; Sirogonium Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 89-96 Uploaded date: 31 May, 2011